A Preliminary Study to Assess Whether Spinal Fusion for Scoliosis Improves Carer-assessed Quality of Life for Children With GMFCS Level IV or V Cerebral Palsy. Issue 3 (April 2016) - Sewell, Mathew D.; Malagelada, Francesc; Wallace, Charlie; Gibson, Alex; Noordeen, Hilali; Tucker, Stewart; Molloy, Sean; Lehovsky, Jan
Abstract : Background: Scoliosis affects 50% of children with Gross Motor Function Classification System (GMFCS) level IV or V cerebral palsy (CP). In children with complex neurodisability following intervention, the WHO considers quality of life (QoL) should be assessed to aid decision-making and assess the effects. This study assesses whether scoliosis surgery improves carer-assessed QoL for children with severe CP. Methods: Retrospective review of 33 children (16 male:17 female) with GMFCS level IV/V CP and significant scoliosis. Fifteen underwent observational treatment during childhood, and 18 underwent surgery. Questionnaire and radiographic data were recorded over a 2-year period. The carer-completed Caregiver Priorities and Child Health Index of Life with Disabilities (CPCHILD) questionnaire was used to assess QoL. Results: In the observational group, Cobb angle and pelvic obliquity increased from 46 (40 to 60) and 8 degrees (0 to 28) to 62 (42 to 94) and 12 degrees (1 to 35). Mean CPCHILD score decreased from 50 (30 to 69) to 48 (27 to 69) ( P <0.05). In the operative group, Cobb angle and pelvic obliquity decreased from 78 (52 to 125) and 14 degrees (1 to 35) to 44 (16 to 76) and 9 degrees (1 to 24). Mean CPCHILD score increased from 45 (20 to 60) to 58 (37 to 76) ( P <0.05). Change in pain, and not presence of associated impairments, was the most significant factor affecting QoL changes for children in both groups. There was no difference in mobility, GMFCS level, feeding, or communication in either group before and after treatment. Conclusions: Nonoperative treatment for children with GMFCS level IV/V CP and a significant scoliosis was associated with a small decrease in carer-assessed QoL over 2 years. Spinal fusion was associated with an increase in QoL. Change in pain was the most significant factor affecting QoL changes, and is therefore an important factor to consider when deciding upon surgery. Level of Evidence: Level III—therapeutic retrospective study.